Application of Akhlaq Education in Implementing Code of Ethics in an Organization: An Empirical Case - Kamri, Nor `Azzah (Jurnal Usuluddin, 2009)
This article studies the akhlaq education which is outlined in Islam. The akhlaq education is examined theoretically and its appropriateness is viewed to be applied in the context of organizational management. This article also encompasses the empirical aspect by addressing Tabung Haji institution as the case study. This article found that Tabung Haji has taken several steps in implementing code of ethics in its organization. It is also found that those steps covered the akhlaq education itself. This finding reflects the appropriateness of akhlaq education to be applied in implementing Islamic code of ethics in organization.